PROBLEMATIC INSTITUTIONS OF SPANISH AND POLISH LEGAL SYSTEMS – A COMPARATIVE AND TERMINOLOGICAL ANALYSIS - DORABIALSKA, Anna Magdalena (Comparative Legilinguistics, 2012)
The article is based on the comparative and terminological analysis of selected examples from the Spanish and the Polish law. The author’s objective is to apply the legal comparative methods to the considerations about equivalents for Polish and Spanish terms and legal concepts. The introduction regards the placement of analized jurisdictions in the classification of legal systems in the world. The main argumentation consists of three parts. The first one refers to the nomenclature of connections between natural or legal persons and a determined legal system. The second section concerns the Inheritance Law and focuses on the legal theory of the concept of the reserved portion in both analized systems. In the last part the author describes the organization of company bodies contrasting the models of Polish and Spanish limited liability companies and joint-stock companies, with reference to the notions introduced in the EU-Law.